2019
DOI: 10.3390/ijerph16203931
|View full text |Cite
|
Sign up to set email alerts
|

A Profile of Injuries Sustained by Firefighters: A Critical Review

Abstract: Firefighters, along with other tactical personnel, are at a high risk of work-related physical injury above that of the private sector. The aim of this critical narrative review was to identify, critically appraise and synthesise key findings from recent literature investigating firefighting musculoskeletal injuries to inform injury reduction programs. The methodological approach (search terms, databases, etc.) was registered with PROSPERO and reported following the Preferred Reporting Items for Systematic Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 42 publications
1
50
0
3
Order By: Relevance
“…These findings also suggest that the use of single-leg and unilateral lower-body strength training can significantly increase bilateral force production when performing lifting tasks. While the back and lower extremities are a leading site of non-fire-related injuries in firefighters and with the mechanism of these injuries often being reported as muscle bending, lifting and squatting or muscle stressing, improvements in absolute lower-body strength may reduce injury risk in this population [8]. This information may be used by firefighters, agencies, and administrators when determining the type of fitness equipment necessary in firehouses or when working with limited budgets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings also suggest that the use of single-leg and unilateral lower-body strength training can significantly increase bilateral force production when performing lifting tasks. While the back and lower extremities are a leading site of non-fire-related injuries in firefighters and with the mechanism of these injuries often being reported as muscle bending, lifting and squatting or muscle stressing, improvements in absolute lower-body strength may reduce injury risk in this population [8]. This information may be used by firefighters, agencies, and administrators when determining the type of fitness equipment necessary in firehouses or when working with limited budgets.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex demands and the dynamic physiological requirements of this occupation, attaining and maintaining an adequate level of physical fitness is of importance in firefighter populations [2,4,6,7]. This requirement is further made evident given that musculoskeletal injuries in the firefighter's workplace are most often caused by 'muscle bending, lifting and squatting, or muscle stressing' [8].…”
Section: Introductionmentioning
confidence: 99%
“…Not only is this form of load carriage known to cause LBP [12], but these injuries are often more severe than those at other bodily sites [13]. Given the load carriage requirements of tactical personnel, it is therefore not surprising that the lower back is a leading site of musculoskeletal injury in these populations [12,14,15]. The workforce impacts of load carriage injuries can be notable with research having identified a significantly greater proportion of absenteeism in police officers, for example, who regularly wore body armor (26%) compared to those who did not (17%) [16] and loads worn by U.S. soldiers deployed to Afghanistan predictive of the development of LBP during deployment [17].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, esta proporción es solo 1.25 veces menor para los trabajadores del sector privado. [17,18] Dentro del análisis de datos se evidencia mayor proporción sintomatológica (50.89%) de la población en esguinces y contracturas con valores significativos de ORA < 1 (ORA = 0.99), al igual que Campbell lo menciona en su estudio prospectivo como síntoma principal. "severidad de la lesión" con el síntoma, obtuvimos que las "fracturas" acumulan un mayor porcentaje de severidad (24.44%) con valor significativo de: ORA >1 (ORA =43), lo que coincide con la investigación de Frost en el año 2015 en la cual manifiesta a las previamente enunciadas como el desorden musculoesquelético más comúnmente reportado (13%).…”
Section: Interpretación De Los Hallazgosunclassified
“…[19] En bomberos como en personal militar la rodilla es el sitio más frecuente para injuria. [18,20] Diversos estudios reportan la rodilla como la ubicación del cuerpo con mayor cantidad de reporte de trastornos musculoesqueléticos, posiblemente el doble que la cifra de lesiones en tobillo. [18,24] En Australia las lesiones de este segmento representan el 30.9% del total de lesiones en bomberos de tiempo completo.…”
Section: Interpretación De Los Hallazgosunclassified